Fast and Reliable Mouse Picking Using Graphics Hardware. (13th April 2009) - Zhao, Hanli; Jin, Xiaogang; Shen, Jianbing; Lu, Shufang
Abstract : Mouse picking is the most commonly used intuitive operation to interact with 3D scenes in a variety of 3D graphics applications. High performance for such operation is necessary in order to provide users with fast responses. This paper proposes a fast and reliable mouse picking algorithm using graphics hardware for 3D triangular scenes. Our approach uses a multi-layer rendering algorithm to perform the picking operation in linear time complexity. The objectspace based ray-triangle intersection test is implemented in a highly parallelized geometry shader. After applying the hardware-supported occlusion queries, only a small number of objects (or sub-objects) are rendered in subsequent layers, which accelerates the picking efficiency. Experimental results demonstrate the high performance of our novel approach. Due to its simplicity, our algorithm can be easily integrated into existing real-time rendering systems.